2009
DOI: 10.1002/stvr.421
|View full text |Cite
|
Sign up to set email alerts
|

Fault localization using a model checker

Abstract: If a program does not fulfill its specification, a model checker can deliver a counterexample. However, although such a counterexample shows how the specification can be violated, it typically comprises large parts of the program and gives little information about which of the visited statements is responsible for the error. In this article, we show that model checkers can also be used to perform model‐based diagnosis and thus fault localization. The approach leads to significantly more precise diagnoses than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Automatic fault localization of imperative programs is a well-known problem, and has been studied from various approaches (cf., Refs. [8], [9], [24], [27]). Among these, coveragebased or spectrum-based debugging [11] is considered a promising method.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic fault localization of imperative programs is a well-known problem, and has been studied from various approaches (cf., Refs. [8], [9], [24], [27]). Among these, coveragebased or spectrum-based debugging [11] is considered a promising method.…”
Section: Introductionmentioning
confidence: 99%
“…2 for a more detailed discussion. Griesmayer et al [24] improve the original implementation to achieve times roughly comparable to our own initial re-implementation (see Sect. 4 for details).…”
Section: Fault Localisationmentioning
confidence: 81%
“…Griesmayer et al have shown that their technique can (in principle) be extended to work with (failing) test cases, but the published results [23] are prohibitively slow, typically executing in hundreds to thousands of seconds per each small benchmark program. Griesmayer et al have improved the original implementation [24] but only achieve times typically in the hundreds of seconds. Approximating model-based fault localisation approaches for test suites, such as Jose and Majumdar's method [34] (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Schupman and Bierre [37] generate short counterexamples for use in fault localisation, where a short counterexample will usually mean fewer uuts for the user to inspect. Griesmayer [38] and Birch et al [39] use model checkers to find failing executions and then look for whether a given number of changes to values of variables can be made to make the counterexample disappear. Gopinath et al [40] compute minimal unsatisfiable cores in a given failing test case, where statements in the core will be given a higher suspiciousness level in the spectra ranking.…”
Section: Related Workmentioning
confidence: 99%